A Multilayer Reservoir Thermal Stratification Module for Earth System Models. (25th October 2019) - Yigzaw, Wondmagegn; Li, Hong‐Yi; Fang, Xing; Leung, L. Ruby; Voisin, Nathalie; Hejazi, Mohamad I.; Demissie, Yonas
Abstract: Thermal stratification in reservoirs is a critical process that regulates downstream riverine energy and biogeochemical cycling. Current stratification models either simplify vertical energy process, reservoir geometry or neglecting the effects of reservoir operation. Here we present a new multilayer reservoir stratification model that can be applied for reservoir and stream temperature simulation at regional or global scale. With a multilayer vertical discretization, we introduce a newly developed storage‐area‐depth dataset to improve parameterization of advection processes in and out of the reservoir. The new model better represents vertical temperature gradient and subsequently temperature of water released to downstream. The stratification model is applied to 1, 400 reservoirs over the contiguous United States and validated against observed surface, profile, and outflow temperature data over 130 reservoirs subjected to various levels of regulation. The Nash‐Sutcliffe values are higher than 0.5 for about 77% of the validated reservoirs using surface temperature while the average values of root mean square error and bias are 3.6 °C and −1.1 °C, respectively. Using the new reservoir storage‐area‐depth dataset improves the simulation of surface temperature at over 69% of the validated reservoirs compared to using simplified reservoir geometry. The reservoir stratification model contributes to improving predictive understanding of anthropogenic impact on terrestrial hydrological, ecological, and biogeochemical cycles. Key Points: A reservoir stratification model including inflow/outflow is developed for future coupling with earth system models Applied to 1, 400 reservoirs in the United States, the model shows good performance against observed surface, profile, and outflow temperature in regulated reservoirs Using a new reservoir storage‐area‐depth dataset improves the simulation of surface temperature compared to using simplified reservoir geometry